2003
DOI: 10.1063/1.1615755
|View full text |Cite
|
Sign up to set email alerts
|

The relative reactivity of CH3D molecules with excited symmetric and antisymmetric stretching vibrations

Abstract: Experimental and theoretical studies explore the reactivity of the symmetric and the antisymmetric stretching vibrations of monodeuterated methane (CH3D). Direct infrared absorption near 3000 cm−1 prepares CH3D molecules in three different vibrationally excited eigenstates that contain different amounts of symmetric C–H stretch (ν1), antisymmetric C–H stretch (ν4), and bending overtone (2ν5) excitation. The reaction of vibrationally excited CH3D with photolytic chlorine atoms (Cl, 2P3/2) yields CH2D products m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
103
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(111 citation statements)
references
References 30 publications
7
103
1
Order By: Relevance
“…Theory predicted that as the Cl atom approaches the H end of CHD 3 , the chemical interaction induces a static curvature coupling (i.e., coupling of a vibrational mode to the reaction coordinate induced by the curvature of the reaction path) between the C-H stretching (v 1 ) motion and the reaction coordinate, resulting in a significant decrease of its frequency in the transition-state region (19)(20)(21)(22) and allowing energy flow between this mode and the reaction coordinate. Similar behavior was found for the CD 3 umbrella mode (v 3 ), yet other modes show little variation in frequencies.…”
Section: Visualizing the Cooperative Atomic Motions While A Chemical mentioning
confidence: 99%
See 2 more Smart Citations
“…Theory predicted that as the Cl atom approaches the H end of CHD 3 , the chemical interaction induces a static curvature coupling (i.e., coupling of a vibrational mode to the reaction coordinate induced by the curvature of the reaction path) between the C-H stretching (v 1 ) motion and the reaction coordinate, resulting in a significant decrease of its frequency in the transition-state region (19)(20)(21)(22) and allowing energy flow between this mode and the reaction coordinate. Similar behavior was found for the CD 3 umbrella mode (v 3 ), yet other modes show little variation in frequencies.…”
Section: Visualizing the Cooperative Atomic Motions While A Chemical mentioning
confidence: 99%
“…By using the reaction path Hamiltonian approach (26), previous ab initio calculations of isotopically analogous reactions mapped out the minimum energy path and the evolution of the vibrational frequencies of various modes along the reaction path (19)(20)(21)(22). By adding the theoretically calculated vibration frequencies (with isotope corrections) to the minimum energy path, we connected the vibrational energy levels according to their symmetries, employing the rule that energy levels for vibration of the same symmetry do not cross (26).…”
Section: Visualizing the Cooperative Atomic Motions While A Chemical mentioning
confidence: 99%
See 1 more Smart Citation
“…[21][22][23][24][25][26][27][28][29][30][31][32] The experimental measurements and dynamical calculations for H-atom abstraction reactions involving simple alkanes illustrate a wealth of dynamical behaviour. For example, the shape of the transition state, with near linear Cl-H-C moiety, is reflected in the low rotational excitation of HCl products; scattering angles are largely determined by impact parameter and their distributions can vary with product rotational and vibrational quantum states; 1 and the reactions of Cl atoms with methane and partially deuterated isotopologues exhibit reagent vibrational mode specificity, [4][5][6][7][9][10][11][12]14,15,[33][34][35][36][37][38][39][40] electronically non-adiabatic pathways, 29,31,41,42 and evidence for scattering resonances. 43 Reactions of functionalized organic molecules (RH = alcohols, 24,44,45 amines, 46 alkyl halides 23,47 and linear and cyclic ethers 24,44,…”
Section: Introductionmentioning
confidence: 99%
“…The reverse reaction of Cl atoms with CH 4 ͑and isotopologs resulting from partial or complete deuteration͒ is well established as a benchmark polyatomic reactive system for studying scattering and vibrational mode and bond specific dynamics. [15][16][17][18][19][20][21][22][23][24] Reaction of Cl * with CH 4 adiabatically correlates with an electronically excited state of the CH 3 radical, and nonadiabatic formation of the energetically accessible CH 3 ͑X 2 A 2 Љ͒ + HCl products is not observed for collisions with energies just above the energetic barrier 25,26 but does occur at much higher collision energies. 27 In studies of the kinetics of collisional processes between Cl * atoms and small hydrocarbons, Matsumi et al 28 demonstrated that the rate of SO quenching of Cl * to grounda͒ Present address: Solar-Terrestrial Environment Laboratory, Nagoya University, Nagoya 464-8601, Japan.…”
Section: Introductionmentioning
confidence: 99%